Evolução da regulamentação de proteção à biodiversidade marinha: uma comparação entre os avanços nos cenários nacional e internacional - Dias, Letícia Custódio (2023)
The importance of protecting marine resources is fully in line with the principle of sustainable development that guides environmental law. In this sense, the main objective of this paper is to compare how advances in the regulation of marine biodiversity protection are being perceived in the national and international scenarios through a comparative analysis